PENERAPAN MODEL CIRC DALAM PEMBELAJARAN TEKS BIOGRAFI PADA PESERTA DIDIK KELAS X SMAN 5 SEMARANG TAHUN PELAJARAN 2023/2024 - Wulandari, Reni Ulfiana; Ngatmini, Ngatmini (Universitas Tanjungpura, 2024)
This research aims to describe the application of the CIRC model in learning biographical texts for class X students at SMAN 5 Semarang for the 2023/2024 academic year. This type of research is descriptive qualitative. This research was carried out in class X-8 with 36 students. This data collection takes the form of test and non-test techniques. The application of this model is divided into initial, content and closing activities. The opening activities started with greetings, prayers, presence and apperception. Content activities, educators form students into groups. Closing activities are carried out by providing conclusions, reflections, follow-up plans, prayers and greetings. Research shows that the CIRC model is appropriate to apply in learning biographical texts. This is supported by the average student score of 89.5. Apart from that, the results of observations and questionnaires show that students can discuss so that learning becomes conducive. This model also makes it easier for students to explain characters in detail. Suggestions for educators, they should use learning models according to the learning material so that learning results are maximized. Keywords: application, writing, biographical text, CIRC Model AbstrakRiset ini bertujuan untuk menggambarkan penerapan model CIRC dalam pembelajaran teks biografi pada peserta didik kelas X SMAN 5 Semarang tahun pelajaran 2023/2024. Jenis penelitian ini adalah kualitatif deskriptif. Penelitian ini dilaksanakan di kelas X-8 dengan 36 peserta didik. Pengumpulan data ini berupa teknik tes dan nontes. Penerapan model ini terbagi atas kegiatan awal, inti, dan penutup. Kegiatan awal dimulai dari salam, doa, presensi, dan apersepsi. Kegiatan inti, pendidik membentuk peserta didik menjadi kelompok untuk menulis teks biografi sesuai tokoh idolanya. Kegiatan penutup dilaksanakan dengan menunjukkan hasil tes peserta didik yang diperoleh yakni 89,5 dan memberikan simpulan, refleksi, rencana tindak lanjut, dan salam. Dari penelitian menyatakan model CIRC tepat diterapkan di pembelajaran teks biografi. Selain itu, hasil observasi dan angket menunjukkan bahwa peserta didik dapat berdiskusi sehingga pembelajaran menjadi kondusif. Model ini juga mempermudah peserta didik memaparkan tokoh dengan rinci. Kata Kunci: penerapan, menulis, teks biografi, Model CIRC